Technology-Based Learning Through Unity Application in Teaching Spatial Volume of Geometric Shapes for 6th Grade Elementary School Students - Alifah Amrinada; Aji Aryo Prayoga; Dea Ayu Ninda Asyifa; Muhammad Rizqi Qurota Ayun; Annisa Hasna Abidah (Journal of Software Engineering, Information and Communication Technology (SEICT), 2022)
Technological advancements require educators to be more innovative in the process of teaching mathematics. Therefore, this journal serves as a renewal in utilizing technological advancements, especially in the field of education. The purpose of this research is to create interactive multimedia that utilizes technology to develop a learning application using Augmented Reality (AR). This research utilizes the Multimedia Development Life Cycle (MDLC) method, which consists of concept, design, material, collecting, assembly, testing, and distribution. Based on the research findings, it can be concluded that the learning media in the form of a Unity application for the mathematical concept of spatial volume can be well-designed through its development method, enabling effective learning to achieve learning objectives.